Perceptions and intentions of Malaysian urbanites towards the concept of retirement village - Lim, Xin Jean (2018)
Retirement village is a novel housing option that offers a new form of retirement living for the elderly, who are aged above 65 years old and able to live independently. Retirement village aims to promote an active and high-quality life during the elderly’s twilight years. Typical features in retirement village include panic buttons, grab bars in the bathroom, and switches at a lower level. Provision of housing for the elderly becomes more significant with a rapid increasing number of ageing population in our country. The concept of retirement village received good response from various western countries but its applicability in eastern countries still scant. Hence, this study intends to fill literature and industry gap by verifying the perception and intention of Malaysian towards the idea of retirement village. This study was grounded by two theories from different scope of research, that are theory of planned behavior (TPB) from psychology field as well as ecological theory of aging (ETA) from gerontology field. Survey questionnaire was distributed to the respondents via face-to-face administrated approach. By using purposive sampling technique, 261 responses were collected. All the respondents were Malaysian who stayed in urban area. Partial least squares (PLS), a variance-based structural equation modeling method was adopted in testing the hypotheses. In SEM-PLS, data was analyzed and interpreted based on two-stage approach: (1) assessment measurement model, and (2) assessment of the structural model. The results supported the model by confirming that attitude, subjective norm and perceived behavioural control were positively associated with retirement village buying intention. The proposed antecedents (i.e., perceived risk, communicability and retirement planning) also found significant influences on TPB’s construct. Next, contextual variable of social sustainability proved to influence buying intention on retirement village. Eventually, religion was found to strengthen the relationship between subjective norm—intention and perceived behavioural control—intention, where the positive relationship are stronger among non-Muslim. This research is significant in a few ways. First, to provide developers insights on ways to position retirement village as well as insights for policy makers to develop appropriate policies in promoting elderly housing. Second, this study also adds knowledge in real estate literature regarding applicability of retirement village concept in Malaysia. Finally, this study uncovers the applicability of theory of planned behavior and ecological theory of aging in explaining Malaysian’s acceptance towards retirement village. On top of that, there are some limitations that offer avenues for future studies. This research merely focuses on Malaysia, limiting its ability to generalize the results. Therefore, future studies are recommended to replicate the model in other Asian countries. Additionally, exploring others variables, such as personality trait, location and rate of investment, might show some interesting implications. Also, it may be informative to take note of residents’ actual experiences living in the village. A longitudinal research is likely to provide valuable results in identifying residents’ level of satisfaction towards retirement villages in Malaysia.